Behavioral, neurocognitive, polysomnographic and cardiometabolic profiles associated with obstructive sleep apnea in adolescents with ADHD. (26th July 2021) - Puzino, Kristina; Bourchtein, Elizaveta; Calhoun, Susan L.; He, Fan; Vgontzas, Alexandros N.; Liao, Duanping; Bixler, Edward O.; Fernandez‐Mendoza, Julio
Abstract : Background: A high comorbidity between attention‐deficit/hyperactivity disorder (ADHD) and obstructive sleep apnea (OSA) as well as similar impairments across neurobehavioral outcomes has been described in children. However, there is a paucity of research examining the comorbidity of these two disorders in adolescents. This study examined the association of OSA with sleep, neurobehavioral, and cardiometabolic outcomes in adolescents with ADHD from the general population. Methods: 421 adolescents (16.9 ± 2.3 years, 53.9% male) underwent 9‐hr polysomnography, neurobehavioral, and physical evaluation. ADHD was ascertained by a parent‐or‐self‐report of a lifetime diagnosis/treatment of ADHD. OSA was defined as an apnea hypopnea index of ≥2 events/hour. Groups of controls ( n = 208), OSA‐alone ( n = 115), ADHD‐alone ( n = 54), and ADHD+OSA ( n = 44) were studied. Multivariable‐adjusted general linear models tested group differences in PSG parameters, neurobehavioral, and cardiometabolic outcomes after controlling for sex, race/ethnicity, age, and/or body mass index percentile. Results: The ADHD+OSA group had significantly longer sleep onset latency, shorter total sleep time, lower sleep efficiency, and higher percent of stage 1 sleep, as compared with all other groups, however, these differences were diminished by excluding adolescents on psychoactive medication. The ADHD‐alone group showed significantly higher periodic limb movements than controls. The ADHD+OSA and ADHD‐alone groups did not significantly differ on any measure of neurocognitive or behavioral functioning. The ADHD+OSA and OSA‐alone groups showed significantly worse cardiometabolic and inflammatory biomarkers when compared to controls or the ADHD‐alone, but did not significantly differ between each other. Conclusions: Adolescents with a diagnosis ADHD+OSA showed phenotypic risk factors for OSA (i.e., overweight/obesity, visceral adiposity, metabolic syndrome, and inflammation) but not worse neurobehavioral outcomes when compared with ADHD‐alone. While comorbidity is possible, these data support that adolescents with a suspicion of ADHD should be screened for OSA, before a diagnosis is reached and psychoactive medication initiated.